Toward Zero Hunger Through Coupled Ecological Sanitation-Agriculture Systems - Ryals, Rebecca; Bischak, Elena; Porterfield, Katherine K.; Heisey, Steven; Jeliazovski, Julie; Kramer, Sasha; Pierre, Suzanne (Frontiers in Sustainable Food Systems, 2021)
Ecological sanitation (EcoSan) systems capture and sanitize human excreta and generate organic nutrient resources that can support more sustainable nutrient management in agricultural ecosystems. An emerging EcoSan system that is implemented in Haiti and several other contexts globally couples container-based household toilets with aerobic, thermophilic composting. This closed loop sanitation system generates organic nutrient resources that can be used as part of an ecological approach to soil nutrient management and thus has the potential to contribute to Sustainable Development Goals 2 (zero hunger), 6 (clean water and sanitation for all), and 13 (climate change solutions). However, the role of organic nutrient resources derived from human excreta in food production is poorly studied. We conducted a greenhouse experiment comparing the impact of feces-derived compost on crop production, soil nutrient cycling, and nutrient losses with two amendments produced from wastewater treatment (pelletized biosolids and biofertilizer), urea, and an unfertilized control. Excreta-derived amendments increased crop yields 2.5 times more than urea, but had differing carry-over effects. After a one-time application of compost, crop production remained elevated throughout all six crop cycles. In contrast, the carry-over of crop response lasted two and four crop cycles for biosolids and biofertilizer, respectively, and was absent for urea. Soil carbon concentration in the compost amended soils increased linearly through time from 2.0 to 2.5%, an effect not seen with other treatments. Soil nitrous oxide emissions factors ranged from 0.3% (compost) to 4.6% (biosolids), while nitrogen leaching losses were lowest for biosolids and highest for urea. These results indicate that excreta-derived compost provides plant available nutrients, while improving soil health through the addition of soil organic carbon. It also improved biogeochemical functions, indicating the potential of excreta-derived compost to close nutrient loops if implemented at larger scales. If captured and safely treated through EcoSan, human feces produced in Haiti can meet up to 13, 22, and 11% of major crop needs of nitrogen, phosphorus, and potassium, respectively.